The Dependence of the Deviation of the Output Stabilized Current of the Resonant Power Supply during Frequency Control in the Systems of Materials Pulse Processing (MCIT: Proceedings of International scientific and practical conference, 2021)
The calculated dependences for determining the deviation of the output current of the resonant power supply of the materials pulsed processing system from a given stabilized value are obtained. The inversely proportional dependence of the output current on the frequency at the input of the series resonant circuit is obtained. These dependencies can be applied for the frequency control of the inverter’s switches commutation which stabilizes the RMS value of the output current. At the close to short circuit modes, the deviation of the output current from the stabilized value does not exceed 2%, and therefore it can be ignored.
Keywords: stabilized RMS current, resonant power supply, frequency control